Procalcitonin: A New Parameter For the Diagnosis of Bacterial Infection and Sepsis - Bülbüller, Nurullah; Doğru, Osman (Fırat University, 2001)
Procalcitonin is a glycoprotein that selectively increases in bacterial infections, sepsis and multiple organ failures. On the other hand, in viral infections, autoimmun infections or operative trauma procalcitonin level does not increase or only slightly increases. Therefore, procalcitonin can be used as a diagnostic parameter in bacterial and nonbacterial infections and as a prognostic parameter in motinorization of critical patients. The literature related to PCT was discused in the study.

Procalcitonin (PCT) selektif olarak bakteriyel inflamasyon, sepsis ve multiorgan yetmezliğinde artan bir glikoproteindir. Buna karşılık viral enfeksiyonlar, otoimmün hastalıklar veya operatif travmada çok az yükselir veya hiç yükselmez. Bu nedenle PCT, bakteriyel ve nonbakteriyel enfeksiyonların ayırımında diagnostik, kritik hastaların monitorizasyonunda da prognostik bir parametre olarak kullanılabilir. Bu çalışmada PCT ile ilgili literatür değerlendirildi.
PROCALCİTONİN: BAKTERİYEL ENFEKSİYON VE SEPSİSİN TEŞHİSİNDE YENİ BİR PARAMETRE